2012
DOI: 10.4236/sgre.2012.34037
|View full text |Cite
|
Sign up to set email alerts
|

Techno-Economic Feasibility Analysis of Solar Photovoltaic Power Generation: A Review

Abstract: With the rapid depletion of fossil fuel reserves, it is feared that the world will soon run out of its energy resources. This is a matter of concern for developing countries whose economy heavily leans on its use of energy. Under the circums-tances it is highly desirable that renewable energy resources should be utilized with maximum conversion efficiency to cope with the ever increasing energy demand. Furthermore, the global economic and political conditions that tend to make countries more dependent on their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Biomass energy has potential as well through gasification, combustion and other methods and applications [17]. Solar energy is considered the most viable and reasonable choice regarding the fact that most of Palestine receives plenty of sun ray in terms of duration and radiation intensity [18].…”
Section: Figure 1 Administrative Areas In Palestinementioning
confidence: 99%
“…Biomass energy has potential as well through gasification, combustion and other methods and applications [17]. Solar energy is considered the most viable and reasonable choice regarding the fact that most of Palestine receives plenty of sun ray in terms of duration and radiation intensity [18].…”
Section: Figure 1 Administrative Areas In Palestinementioning
confidence: 99%
“…To assess the techno-economics of individual decentralized technologies, evaluating the technological appropriateness and the associated economic viability of each technology for a successful application are needed [6]. In their analysis in 2011, Szabó et al showed the levelized cost of electricity (LCOE) calculated for local mini-grid photovoltaic (PV) systems in Africa ranges from approximately 0.2 to 0.55 $/kWh [7,8].…”
Section: Techno-economics Of Mini-grids In Sub-saharan Africamentioning
confidence: 99%
“…There are papers about the study of the techno-economy of public street lightings by various authors, such as Velaga and Kumar [4], Kusumayogo et al [5], Sihombing and Kasim [6], and Jamil et al [7]. Ahmad [8] and Al-Salaymeh et al [9] studied the technical and economic assessment of photovoltaic in residential buildings.…”
Section: Introductionmentioning
confidence: 99%